2015
DOI: 10.1093/arclin/acv001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Brief, Water-Based Exercise Intervention on Cognitive Function in Older Adults

Abstract: Physical inactivity is a modifiable risk factor for accelerated cognitive decline in older adults. Water-based exercise provides the same physiological benefits as land-based exercise with reduced risk of acute injury. The current study evaluated the effects of a brief, water-based exercise intervention on cognitive functioning and cardiovascular fitness in a group of community dwelling older adults. The exercise group (n = 27, M(age) = 63.26 ± 7.64, 78% female) attended one moderate intensity water aerobics c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 125 publications
1
7
0
3
Order By: Relevance
“…The present study has several limitations that could affect ecological validity. In this regard, the small sample size, while similar to that of numerous previous studies (Fedor et al, 2015;Jung et al, 2014;Means and O Sullivan, 2000;Sato et al, 2015) serves as proof-of-concept evidence for the effect of the effect combined aquatic and cognitive training on quality of life, fall self-efficacy and motor performance (static and dynamic balance) in aged with varying cognitive status levels. In addition, several extraneous variables could affect quality of life, fall self-efficacy and motor performance (static and dynamic balance).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The present study has several limitations that could affect ecological validity. In this regard, the small sample size, while similar to that of numerous previous studies (Fedor et al, 2015;Jung et al, 2014;Means and O Sullivan, 2000;Sato et al, 2015) serves as proof-of-concept evidence for the effect of the effect combined aquatic and cognitive training on quality of life, fall self-efficacy and motor performance (static and dynamic balance) in aged with varying cognitive status levels. In addition, several extraneous variables could affect quality of life, fall self-efficacy and motor performance (static and dynamic balance).…”
Section: Discussionsupporting
confidence: 69%
“…Problematically, while studies investigating the impact of aquatic exercise on cognition are scarce (Ayán et al, 2017), and no studies have been performed on a subgroup analysis of the effects of exercise interventions on different cognitive domains of the elderly (Zhou et al, 2018). In addition, since water-based exercise provides the same physiological benefits as land-based exercise with reduced risk of acute injury (Fedor et al, 2015), especially from falls, the present study novely attempted to determine if a multimodal therapy of aquatic exercise and cognitive training could improve on motor performance and quality of life in aged. Further, the present study uniquely attempted to determine if this multimodal therapy is more effective on those with low or high cognitive status in order to individualize and target program design.…”
Section: Introductionmentioning
confidence: 99%
“…Both papers were published after the present study was carried out. In this vein, Fedor 4 found that one week of water aerobics produced significant increases in the executive function, attention, and memory performance of community dwelling older adults. Similarly, Sato 17 observed that a weekly water-based exercise programme (including water cognitive tasks) for the duration of ten weeks, improved several cognitive functions, such as attention and memory in healthy elderly people.…”
Section: Patterns In Sscgmentioning
confidence: 99%
“…For instance, swimming pool-based exercise stands as one of the most appealing options for the elderly. Nevertheless, very few research studies have endeavoured to pinpoint their effects on the cognitive functions of this population in particular 4 . In addition, very little is known about the influence training programmes that combine land-based and water-based exercises might have on the cognitive function of healthy older people 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The exercise group scored statistically higher (P < .05 or better) on cardiorespiratory fitness and batteries of executive function. 68 Cardiovascular fitness improved in the exercised group as well, surprising findings given the short 1-week treatment duration.…”
Section: Aquatic Therapy Use In Dementiamentioning
confidence: 88%